PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPOSISI MELALUI PENERAPAN METODE TEAM ASSISTED INDIVIDUALIZATION PADA SISWA KELAS X TKJ 2 SMKN 1 KARANGANYAR NGAWI - Supangat, Supangat; Hadi, Panji Kuncoro; Soleh, Dwi Rohman (Universitas PGRI Madiun, 2024)
This study aims to improve students' exposition text writing skills through the application of the Team Assisted Individualization method among the tenth-grade TKJ 2 students at SMKN 1 Karanganyar, Ngawi Regency. This research is a Classroom Action Research consisting of three cycles. The data sources for this research include events, the learning process, information, and documentation. Data collection techniques encompass observation, assignments, in-depth interviews, and document analysis. The results of the study indicate that the application of the Team Assisted Individualization method can improve the exposition text writing skills of the tenth-grade TKJ 2 students at SMKN 1 Karanganyar, as evidenced by the increasing number of students meeting the Minimum Competency Criteria (KKTP). In the Pre-cycle, 16.67% of students met the criteria. In Cycle I, exposition writing skills proficiency reached 33.33%, in Cycle II it reached 66.67%, and in Cycle III it reached 86.67%.This study aims to improve students' exposition text writing skills through the application of the Team Assisted Individualization method among the tenth-grade TKJ 2 students at SMKN 1 Karanganyar, Ngawi Regency. This research is a Classroom Action Research consisting of three cycles. The data sources for this research include events, the learning process, information, and documentation. Data collection techniques encompass observation, assignments, in-depth interviews, and document analysis. The results of the study indicate that the application of the Team Assisted Individualization method can improve the exposition text writing skills of the tenth-grade TKJ 2 students at SMKN 1 Karanganyar, as evidenced by the increasing number of students meeting the Minimum Competency Criteria (KKTP). In the Pre-cycle, 16.67% of students met the criteria. In Cycle I, exposition writing skills proficiency reached 33.33%, in Cycle II it reached 66.67%, and in Cycle III it reached 86.67%.Penelitian ini bertujuan untuk meningkatkan keterampilan menulis teks eksposisi siswa melalui penerapan metode Team Assisted Individualization pada siswa kelas X TKJ 2 SMKN 1 Karanganyar Kabupaten Ngawi. Penelitian ini merupakan Penelitian Tindakan Kelas yang terdiri dari 3 siklus. Sumber data penelitian ini adalah peristiwa, proses pembelajaran, informasi, dan dokumentasi. Teknik pengumpulan data meliputi pengamatan, pemberian tugas, wawancara mendalam, dan analisis dokumen. Hasil penelitian menunjukkan bahwa penerapan metode Team Assisted Individualization dapat meningkatkan keterampilan menulis teks eksposisi pada siswa kelas X TKJ 2 SMKN 1 Karanganyar yang ditandai dengan peningkatan jumlah siswa yang tuntas. Pada Prasiklus 16,67% siswa yang tuntas. Siklus I keterampilan menulis eksposisi mencapai 33,33%, siklus II mencapai 66,67% dan siklus III mencapai 86,67% siswa yang tuntas.